Effectiveness of the Job Market Fair in Reducing Unemployment Rates - Mauliddah, Nurullaili; Mochklas, Mochamad; Rosmaniar, Asyidatur (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2022)
The study aims determine the effectiveness of the JMF in lowering the unemployment rate. Based on the purposive sampling technique, this studi use descriptive qualitative approach with SWOT analysis to analyze a portrait of strengths, weaknesses, and opportunities and macro and micro challenges to the effectiveness of job market fair implementation in reducing unemployment. The result of this study known that JMF was an alternative in reducing the unemployment rate. Its effectiveness was still relatively moderate through the development of community economic independence, such as helping young people to build independent businesses to form start-ups, so they do not only depend on formal jobs.Keywords: Job market fair; unemployment rate